EFEKTIVITAS CODE OF CONDUCT FOR RESPONSIBLE FISHERIES DI SAMUDERA HINDIA STUDI KASUS: KERJASAMA INDONESIA DAN AUSTRALIA MENANGGULANGI ILLEGAL UNREGULATED UNREPORTED (IUU) FISHING - Salfauz, Claudiya Radekna; Utomo, Tri Cahyo; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Illegal fishing has become an important issue because it threatens themaritime security. The activity of illegal unregulated unreported(IUU) fishing in the Indian Ocean not only does it jeopardize themaritime security of Indonesia and Australia, but also does it causefinancial deficit to the country, moreover, if the activity of IUU fishingkeeps increasing it will endanger the sustainability both fish andenvironment. The situation encourages member countries of Food andAgriculture Organization (FAO) in devising an applicable concept tomany countries in the world regarding organized, responsible, andsustainable fisheries management and development, namely Code ofConduct for Responsible Fisheries (CCRF) which was settled in 1995.The activity of IUU Fishing in the Indian Ocean initiates Indonesiaand Australia to conduct a fisheries cooperation agreement toprevent, deter and eliminate illegal fishing in the Indian Ocean.Indonesia and Australia adopt the CCRF into the fisheries treaty. Thisresearch aims to identify the efficacy of CCRF implementation in thefisheries cooperation agreement between Indonesia and AustraliaGovernment to cope with IUU fishing. The result of the researchshows that CCRF as a regime is able to work effectively to cope withIUU fishing in the Indian Ocean.